The impact of mangrove forest density on marine debris accumulation: Implications for ecosystem health and sustainable coastal management - Werorilangi, Shinta; Saru, Amran; Wiwiyani (Jurnal Bisnis Kehutanan dan Lingkungan, 2025)
Background: Marine debris refers to all solid materials resulting from human activities that are found in aquatic environments, such as oceans, seas, and coastal areas. These materials directly threaten aquatic ecosystems' health and productivity and require specific actions to prevent and mitigate their negative impacts. In mangrove ecosystems, the density of mangrove vegetation may influence the accumulation of marine debris. This study investigates the relationship between mangrove density and the abundance and types of marine debris around Kassikebo Pier, Pangkep Regency. Methods: The research employed the parallel line method for sampling marine debris and a 10 m x 10 m transect for assessing mangrove density. The study was conducted across three stations with varying mangrove densities: sparse, medium, and dense. The abundance and percentage mass of debris were calculated based on size and type. Physical oceanographic parameters were also measured, such as current direction, velocity, and tidal patterns. The mangrove species were identified, and their densities were analyzed to determine their correlation with marine debris abundance. Findings: The study revealed that macro-sized debris dominated across all stations. At Station 1 (sparse mangrove density), the abundance of macro debris was 0.45 pieces/m² and 7.97 grams/m²; at Station 2 (medium density), it was 0.66 pieces/m² and 14.75 grams/m²; and at Station 3 (dense mangrove density), it was 1.05 pieces/m² and 21.48 grams/m². Plastic was the most dominant type of debris at all stations. The mangrove species identified in the area included Avicennia alba, Avicennia marina, and Rhizophora mucronata, with Avicennia alba being the most abundant. Conclusions: The study found a positive correlation between mangrove density and the abundance of marine debris, indicating that denser mangroves tend to trap more debris. Novelty/originality of this article: his research highlights the link between mangrove density and marine debris accumulation, stressing the need for plastic waste management in mangrove-rich areas. It offers recommendations for local governments and communities to adopt the 3R approach.